Adler Planetarium and Astronomical Museum (Curt Teich & Co., Inc.)
Lake Front Island off Grant Park. The only institution of its kind in this country. This is the gift of Max Adler. Its huge planetarium instrument reproduces the sky and all the celestial movements in miniature and its museum contains many items of historical interest and models to illustrate modern methods of observing.